PENGEMBANGAN MULTIMEDIA PEMBELAJARAN UNTUK MENINGKATKAN RASA INGIN TAHU DAN BERPIKIR KRITIS SISWA SD - Nur Wenda, Dhian Dwi; Mukmin, Bagus Amirul (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
This research aims to develop a valid, practical, and effective learning multimedia to enhance students' curiosity and critical thinking skills in the fourth grade of elementary school. The background of the study indicates that curiosity and critical thinking skills among students at SDN Lirboyo 4 are still low, with only 30% of students demonstrating good curiosity behaviors and only 23% having adequate critical thinking skills. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results show that the developed multimedia product received an average validation score of 85% from media experts and 82% from elementary school learning strategy experts, which is categorized as very valid. The product's practicality test, based on teacher response questionnaires, shows an average score of 87%, also falling into the very practical category. Additionally, the product's effectiveness test indicates that after using the multimedia, students' curiosity skills scored 85, and their critical thinking skills scored 83. These scores reflect a significant improvement beyond the minimum completion criteria (75) established by the school. Thus, the learning multimedia developed in this study is proven to be valid, practical, and effective in increasing the curiosity and critical thinking skills of fourth grade students at SDN Lirboyo 4, Kediri City.